Power hedging and faith fetters: The factors of tribe and religion in Afghanistan's state building - Chang, Li; Pengtao, Geng; Xiyao, Zhang (Frontiers in Political Science, 2022)
In recent years, Afghanistan has experienced sustained political instability that is rooted in a relatively low level of modern nation-state building. The traditional tribal and Islamic conservationists are too powerful and restrict the process of nation-state building in Afghanistan. The logic behind a traditional tribal society and a modern nation-state is different, and their power has inherent contradictions in terms of attributes, vectors, and fields of action. The religious conservative tendency fetters the modernization of Afghanistan in different aspects, and the absolute religious right negates national power in concept. In reality, the localization of teaching law eliminates national ability, and fundamentalism stifles the vitality of society. The tribal and religious policies of the new Taliban government will shape the future of Afghanistan politics.